Perceptions of 1st-Year MBBS Students about the Medical Council of India Mandated Foundation Course - Sujata Sethi; Piyush Verma; Vivek Srivastava; Rakesh Mittal (Wolters Kluwer Medknow Publications, 2021)
Background: Foundation course (FC) program was introduced recently by the Medical Council of India for the 1st-year of MBBS students in India to serve as a bridge into the MBBS program as well as to orient the students to various aspects of the medical college environment. Aim: The aim of the study was to analyze the feedback on FC by the 1st-year MBBS students. Materials and Methods: The study was conducted at the Pt. B. D. Sharma PGIMS, Rohtak, during August 1-31, 2019, involving 242 1st-year MBBS students. At the end of each day of the program, the students received a multiple-choice questionnaire along with a feedback form. Further, at the end of the 1-month of the FC program, the students received a final feedback form reflecting upon various aspects of the FC. Results: Majority of the students felt that the FC was well organized and helpful in gaining knowledge and information. Basic life support was the "most preferred" skill session (68.5%), followed by a session on immunization clinic (31.6%). Students felt that the training sessions organized under the six modules of the FC were able to impart ample information on respective topics and were considered helpful to a great extent for majority of the students. Fifty-eight percent of the students felt content overload and rushed pace of content delivery did not help in learning. Other hindering factors recognized by students included excessive use of technical/medical terminology, audio-visual disturbances, and spread out locations for small group activities. Conclusions: High levels of satisfaction with the FC in general and in terms of content and organization were observed. Shortcomings recognized through feedback will help us to improve.